Generation of h–Shaped pulse in a mode–Locked erbium-doped fiber laser - Liu, Chao; Li, Guoru; Su, Xiancui; Wang, Yiran; Gao, Feilong; Xie, Yiyan; Kumar, Santosh; Zhang, Bingyuan (Frontiers in Physics, 2022)
In this paper, the generation of h-shaped pulse is demonstrated in a nonlinear polarization rotation (NPR) mode-locked erbium-doped fiber laser (MLEDFL). The length of the entire cavity is about 2506 m to enhance the nonlinear effect in the cavity. The multi-pulse state is obtained firstly under the certain pump power and polarization state. By further adjusting the polarization controller (PC), the h-shaped pulse with sharp top and flat bottom is generated under the pump power of 100 mW. And the duration of pulse is tuned with a range of 54.63 470 ns. The width and intensity of pulse trailing part vary differently during the process of increasing pulse width. The results indicate that the peak power clamping effect and weak birefringence effect dominate in different h-shaped pulse forming process.